The red chief - Idriess, Ion L. (Ion Llewellyn), 1890-1979. (Melbourne : Bolinda Press, Australian Large Print Audio & Video, 1998)
It would be hard to find a more satisfying hero than the young warrior Red Kangaroo, who by his mental and physical prowess became a chief of his tribe - the revered and powerful Red Chief of the Gunnedah district. His story is a first rate tale of adventure but it is something more - a true story handed down from generation to generation by its hero's tribe and given by the last survivor, "King" Bungaree, to the white settlers of the district. Haunted by the knowledge of "a good story... a story from a fast dying race, a whisper from the primitive past", Ion Idriess has called back that vanishing world to vivid and exciting life, while preserving one of the few true histories of the Aboriginal people.
'First published by Angus & Robertson Publishers, Australia, 1953.
Keywords: Aboriginal Australians -- New South Wales -- Gunnedah Region -- Folklore; Large print books